2017
DOI: 10.3168/jds.2016-11796
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary infusion of Escherichia coli lipopolysaccharide negatively affects feed intake, chewing, and clinical variables, but some effects are stronger in cows experiencing subacute rumen acidosis

Abstract: Feeding high-grain diets increases the risk of subacute rumen acidosis (SARA) and adversely affects rumen health. This condition might impair the responsiveness of cows when they are exposed to external infectious stimuli such as lipopolysaccharide (LPS). The main objective of this study was to evaluate various responses to intramammary LPS infusion in healthy dairy cows and those experimentally subjected to SARA. Eighteen early-lactating Simmental cows were subjected to SARA (n = 12) or control (CON; n = 6) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
(67 reference statements)
7
25
1
Order By: Relevance
“…Moreover, milk constituent analysis showed that challenged S. aureus led to a reduction in the content of milk fat, lactose and dry matter, and increase the content of milk protein after S. aureus infusion, where some changes in milk constituents were more pronounced in SARA-positive than SARAnegative cows. The result was similar to that reported by S. Aditya [43] . Bovine mastitis is often caused by infection with environmental pathogens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, milk constituent analysis showed that challenged S. aureus led to a reduction in the content of milk fat, lactose and dry matter, and increase the content of milk protein after S. aureus infusion, where some changes in milk constituents were more pronounced in SARA-positive than SARAnegative cows. The result was similar to that reported by S. Aditya [43] . Bovine mastitis is often caused by infection with environmental pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…Infusion with S. aureus induced a strong increase in SCC, and the number of SCC in SARA-positive cows was slightly higher than the SCC in SARA-negative cows. S. Aditya et al, showed no difference in the levels of SCC in control and SARA cows after mammary gland infusion of LPS [43] . In addition, the P.N.…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, our findings suggest that histamine induces the inflammatory response of bovine rumen epithelial cells through the NF-κB pathway, which provide novel insights into the molecular mechanisms of rumenitis in SARA cows. Furthermore, there are substantial amounts of inflammatory inducers, including volatile fatty acids and lipopolysaccharide, also produced in the rumen of SARA cows, which induces rumen inflammation that may further mediate the development of SARA [18,32]. Therefore, it will be interesting to explore the specific role of these inflammatory inducers in the development of SARA in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind using ruminal temperature as an indicator of SARA is that, during intensive fermentation phases, significant amounts of heat are produced in parallel to SCFA accumulation and pH drop. On the other hand, ruminal temperature is tightly related to overall body temperature, too (Aditya et al., ). Studies conducted by AlZahal et al.…”
Section: Interpretation Of Ruminal Temperaturementioning
confidence: 99%